Design and synthesis of N-[6-(Substituted Aminoethylideneamino)-2-Hydroxyindan-1-yl]arylamides as selective and potent muscarinic M1 agonists. Issue 19 (1st October 2015) - Liu, Bin; Croy, Carrie H.; Hitchcock, Stephen A.; Allen, Jennifer R.; Rao, Zhigang; Evans, David; Bures, Mark G.; McKinzie, David L.; Watt, Marla Leigh; Stuart Gregory, G.; Hansen, Marvin M.; Hoogestraat, Paul J.; et al.
Graphical abstract: Abstract: The observation that cholinergic deafferentation of circuits projecting from forebrain basal nuclei to frontal and hippocampal circuits occurs in Alzheimer's disease has led to drug-targeting of muscarinic M1 receptors to alleviate cognitive symptoms. The high homology within the acetylcholine binding domain of this family however has made receptor-selective ligand development challenging. This work presents the synthesis scheme, pharmacokinetic and structure–activity-relationship study findings for M1 -selective ligand, LY593093. Pharmacologically the compound acts as an orthosteric ligand. The homology modeling work presented however will illustrate that compound binding spans from the acetylcholine pocket to the extracellular loops of the receptor, a common allosteric vestibule for the muscarinic protein family. Altogether LY593093 represents a growing class of multi-topic ligands which interact with the receptors in both the ortho- and allosteric binding sites, but which exert their activation mechanism as an orthosteric ligand.